IRF5, but not TLR4, DEFEB1, or VDR, is associated with the risk of ulcerative colitis in a Han Chinese population. (October 2013) - Li, Pan; Lv, Hong; Yang, Hong; Qian, Jia-Ming
Abstract Objective. IRF5, TLR4, DEFB1, and VDR genetic variations have been associated with ulcerative colitis (UC) in several European patient cohorts. As distinct genetic backgrounds may play a role in different ethnicities, we evaluated the effects of single-nucleotide polymorphisms (SNPs) in these genes and their interactions in UC patients of Han Chinese descent. Material and methods. DNA samples from 300 UC patients and 302 healthy control subjects from Peking Union Medical College Hospital were genotyped for 14 tag SNPs, which were selected based on haplotype analysis of IRF5, TLR4, DEFB1, and VDR. Multidimensionality reductions were used to explore gene–gene interactions. Results. The only observed association with UC was for IRF5. On an allelic level, SNP rs3807306 was associated with UC risk (p = 6.7 × 10−3). On a genotypic level, the CC genotype of SNP rs3807306 (p = 0.03) was associated with protection from UC, and the AA genotype of SNP rs4728142 (p = 7.6 × 10−3) was associated with a risk of UC. In the haplotype analysis, GGATT was highly correlated with UC risk (p-Value = 2.0 × 10−4). No significant multilocus interactions were detected among these four genes. Conclusions. Our study confirmed the association of IRF5 with UC in Han Chinese patients. Han Chinese UC patients share part of their genetic susceptibility with Caucasian patients.